2017
DOI: 10.1007/s00484-017-1375-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest

Abstract: Canopy temperature is a result of the canopy energy balance and is driven by climate conditions, plant architecture, and plant-controlled transpiration. Here, we evaluated canopy temperature in a rubber plantation (RP) and tropical rainforest (TR) in Xishuangbanna, southwestern China. An infrared temperature sensor was installed at each site to measure canopy temperature. In the dry season, the maximum differences (T - T) between canopy temperature (T) and air temperature (T) in the RP and TR were 2.6 and 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…In terms of the yearly time series, the same results were found, with the exception of the period between June and November of 2014. Song et al (2017) found in their one-year data analysis of the canopy temperature difference between Tc and Ta at these two sites that the differences at the RP site were higher than those of the TR site throughout the whole year. When we analysed the five-year data related to the canopy temperature depression between Tc and Ta, the same results were observed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In terms of the yearly time series, the same results were found, with the exception of the period between June and November of 2014. Song et al (2017) found in their one-year data analysis of the canopy temperature difference between Tc and Ta at these two sites that the differences at the RP site were higher than those of the TR site throughout the whole year. When we analysed the five-year data related to the canopy temperature depression between Tc and Ta, the same results were observed.…”
Section: Discussionmentioning
confidence: 93%
“…At the vegetation level, canopy height and structure affected the Tc (Greco et al 2012). Song et al (2017) found that a normalised condition (Tc-Ta) was very sensitive to all simulated meteorological conditions that were linearly, directly proportional to solar radiation and inversely proportional with the vapor pressure deficit (VPD) and also non-linearly, inversely proportional to Ta and wind speed (Ws). Canopy height had a large influence on (Tc-Ta), in that it decreased with increasing height and increased in very low vegetation under drought stress (Greco et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, according to many other studies [46][47][48][49][50][51][52][53][54], we can conclude that heterogeneity of canopy temperature mainly results from physical and biological interactions, which are affected by climatic conditions (such as wind, temperature, vapor-pressure deficit, relative humidity, long wave radiation, and the angle of radiation incident on the leaf surface), environmental conditions (soil temperature at 2 cm depth, soil moisture, adjacent objects, and solar height), canopy structure complexity (leaf inclination distribution frequency, size, shape, and position), canopy parameters (canopy albedo, emissivity, and stomatal resistance) and ecosystem functions (evapotranspiration and photosynthesis). Among these studies, the result of Smith and Carter [47] showed that the temperatures of needle-leaf were closer to air temperature than that of broad leaves, and needle leaves usually remained within 4-8 K of air temperature, whereas Jones [48] reported that sunlit broadleaves might be 10-15 K higher than air temperatures.…”
Section: Discussionmentioning
confidence: 99%